LEEP in Action: The Lawrence Environmental Education Project - Griswold, Wendy (Kansas State University, 2010)
Title: LEEP in Action: The Lawrence Environmental Education Project Author: Wendy Griswold, Center for Hazardous Substance Research, Kansas State University Abstract Community education plays a key role in informing the public about issues and opportunities related to sustainability. The Lawrence Environmental Education Project (LEEP) provides family-friendly educational activities designed to illuminate current environmental issues and encourage participants to take action. LEEP program includes community field trips and an eco-literacy book club. This poster presentation highlights local community based efforts to engage citizens in discussions and activities to advance sustainability.
Keywords: Education; Communities (Place based or human); Environment